Pengembangan Learning Management System Sebagai Media Pembelajaran Untuk Peserta Pelatihan Desain Grafis Di Balai Latihan Kerja Singosari - Zidan, Herfyan Omar; Adi, Eka Pramono; Fajarianto, Otto (Journal of Educational Technology Studies and Applied Research, 2024)
This research aims to develop a web-based Learning Management System (LMS) as a learning medium for graphic design trainees at Singosari Vocational Training Center (BLK). The LMS is expected to increase access and flexibility of learning for participants, as well as facilitate instructors in delivering materials and assignments in a structured manner. The LMS development was conducted using the ADDIE model which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The results of the media expert validation stated that all aspects were valid, while the material expert stated that all aspects were valid. The responses of the trainees also showed very good results and the majority of participants experienced improvement in learning. This LMS is effective to be used as learning media in graphic design training, especially to support distance learning.